УПРАВЛЕНИЕ ПРОФИЦИТОМ БЮДЖЕТА И ФИСКАЛЬНАЯ «ТОНКАЯ НАСТРОЙКА» - Афанасьев, Мстислав; Шаш, Наталия (Вопросы государственного и муниципального управления, 2020)
The subject of research of this paper is the specifics of forming and managing a budget surplus when providing economic growth for the national economy. The results of analyzing the concepts of a budget balance are presented, and directions for managing a positive balance of the state budget are revealed. The specifics of the macroeconomic politics of a surplus are given, and it is revealed that forming a “new” fiscal regime – surplus regime – requires a radical restructuring of budget management. The general typical features of countries with a long-term period of a budget surplus are revealed: focus on budget consolidation on the expenditure side of the budget and the ensuing complex budget reforms made after achieving a surplus. It is discovered that one of the main reasons for supporting a stable surplus budget in a number of the world’s countries is the radical restructuring of economic and financial priorities, which was caused by serious macroeconomic shocks. It is noted that when assessing the possibility of maintaining a budget surplus in specific countries, it should be taken into account that unfavorable macroeconomic events such as the financial crisis of 2008 or the global pandemic of COVID-19 in the current year (2020) are of crucial significance for maintaining a surplus. According to the results of a comparative analysis of the dynamics of the level of budget deficit and the rates of economic growth, using the example of Switzerland and Norway for 2009–2019, no direct correlation between these indicators was discovered, and it was concluded that there was a lack of empirical evidence and appropriate theoretical generalizations about the existence of a cause-and-effect relationship between economic growth and the type of balance (deficit, surplus, “zero-based”) of the state budget. The advisability of using the budget surplus to reduce the tax burden and to reduce the level of state debt was assessed.